Towards transforming community eye care: an observational study and time-series analysis of optometrists' prescribing for eye disorders. (July 2021) - Jonuscheit, S.; Geue, C.; Laidlaw, R.; Fischbacher, C.; Melia, B.; Lewsey, J.; King, C.
Abstract: Objectives: This study aimed to provide evidence on the therapeutic prescribing activity by community optometrists in Scotland and to determine its impact on workload in general practice and ophthalmology clinics. Study design: Scottish administrative healthcare data for a 53-month period (November 2013–April 2018) were used to analyse non-medical prescribing practice by optometrists. Methods: Using interrupted time-series regression (Autoregressive Integrated Moving Average), we assessed the impact of optometrist prescribing on ophthalmology outpatient attendances and general practice prescribing for eye disorders. Results: A total of 54, 246 items were prescribed by 205 optometrists over the study period. Since the commencement of data recording, optometrist prescribing activity increased steadily from a baseline of zero to 1.2% of all ophthalmic items prescribed. Neither the monthly number of items prescribed nor the size of optometric workforce were associated with a reduction in ophthalmology outpatient appointments over time. Conclusions: Optometrists increasingly contribute to community ophthalmic prescribing in Scotland, releasing capacity and lessening general practice, but not secondary care workload. There appears to be an underutilisation of optometrists related to the management of dry eye, which represents an opportunity to release further capacity.